Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 37


$x=-4$ or $x=3$

Work Step by Step

$x^{2}+x-12$ =$x^{2} + 4x - 3x -12$ =$x(x+4)-3(x+4)$ =$(x+4)(x-3)$ $x=-4$ or $x=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.